Advances in surgical pathology. - Attanoos, Richard L. (Advances in surgical pathology series, 2014)
"This volume of the Advances in Surgical Pathology Series is a concise, updated review of the pathological characteristics of mesothelioma. It emphasizes the histologic correlation, clinical management, and treatment of mesothelioma. It features current and emerging concepts in the field, which includes recognition of precursor mesothelial lesions, the role of molecular biology in the diagnosis and prognosis of mesothelioma, the interface between the clinician and the surgical pathologist, and the legal implications in relation to disease attributibility to asbestos and other factors. The book provides a resource for the timely updates in knowledge that are necessary for daily practice, for current credentialing, and for the self-assessment modules for recertification (MOC)."--Provided by publisher.